Synthesis and application of streptavidin functionalized organosilica microparticles. Issue 9 (18th October 2014) - Hou, Cailing; Zhang, Linxia; Wang, Yue; Wang, Zhimin
ABSTRACT This article reports on the chemical synthesis, functionalization and application of streptavidin (SA)‐coated organosilica microparticles. Thiol‐functionalized organosilica microparticles are synthesized via a two‐step approach involving acid‐catalyzed hydrolysis and condensation of 3‐mercaptopropyl trimethoxysilane (MPS), followed by base‐catalyzed condensation. The surfaces of these particles are modified with 3‐aminopropyltriethoxysilane (APS), and characterized by FTIR, XPS, and TGA. Then, APS‐functionalized microparticles are covalently coated with SAs by using glutaraldehyde as a coupling agent, and characterized by FTIR, SEM, and AFM. Immobilization of biotinylated λ DNA onto microparticles via SA‐biotin immuoreaction is confirmed by confocal microscopy. The results show that these SA‐functionalized organosilica microparticles are useful carriers for DNA manipulation at the single molecule level. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41560.